2005
DOI: 10.1111/j.1600-9657.2005.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical education undergraduates and dental trauma knowledge

Abstract: The aim of the present study was to assess the level of knowledge of undergraduates from the College of Physical Education (Toledo, Araçatuba) concerning dental avulsion injuries. Data showed that 95% of the respondents did not know what dental avulsion is, 73.5% said they know how to define dental replantation, however, only 26% were able to do it correctly. When asked about first emergency measures after an avulsion, 50% of the respondents said they know what they should do, and the most cited measure was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
77
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 16 publications
10
77
0
9
Order By: Relevance
“…The results of this study confirmed the lack of knowledge about dental trauma in the training of elementary school teachers, similarly to international [2,12,25] and Brazilian [27,31,32] studies. During the academic training of teachers, 47% had first aid training that not addressed the issue of dental trauma and 78% of teachers were unaware of it.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study confirmed the lack of knowledge about dental trauma in the training of elementary school teachers, similarly to international [2,12,25] and Brazilian [27,31,32] studies. During the academic training of teachers, 47% had first aid training that not addressed the issue of dental trauma and 78% of teachers were unaware of it.…”
Section: Discussionsupporting
confidence: 84%
“…W hereas a favorable prognosis for av ulsed / replanted depends significantly on the triad time the tooth remained outside the mouth, storage and appropriate transport medium, and minimal aggression to the root surface, knowledge of the emergency care of traumatic injuries is essential for tooth reestablishment and permanence in the mouth [19,29,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…Torna-se imperioso considerar o tempo em que um dente permanece fora do alvéolo, ou seja, o intervalo de tempo decorrido entre a avulsão e o . Esse tempo deve ser de, no máximo, duas horas, já que a cicatrização depende da sobrevivência das células do ligamento periodontal ao longo da superfí cie radicular 18,19 . Verifi cou-se ainda que 58,8% dos profi ssionais entrevistados relataram escolher como meio de conservação para o dente avulsionado a água da torneira.…”
Section: Discussionunclassified
“…Many studies have shown that there is an insufficient knowledge with regards to immediate management to patients with traumatic dental injuries. This particular study was planned to explore the awareness of the dental professionals about the management of an avulsed tooth/ teeth [12][13][14].…”
Section: Introductionmentioning
confidence: 99%